Polymorphisms of C242T and A640G in CYBA gene and the risk of coronary artery disease: a meta-analysis. - Qiumei Xu (Public Library of Science (PLoS), 2014)
Background Coronary artery disease (CAD) is a leading cause of mortality in many countries. Considerable studies have been carried out to investigate the relationship between the C242T and A640G polymorphisms of CYBA gene and CAD, but the results were still inconsistent. Hence we conducted a meta-analysis to clarify the association. Methods and results A total of 21 eligible literatures were included in the meta-analysis. We observed a significant decreased risk of CAD for C242T polymorphism in Asian population under an allelic model (OR 0.75; 95% CI 0.67-0.84) and a dominant model (OR 0.69; 95% CI 0.61-0.79), however, in overall population and other population no significant association was revealed. We also found A640G polymorphism may contribute to reducing CAD risk under an allelic model (OR 0.84; 95% CI 0.75-0.93), dominant model (OR0.77; 95% CI 0.64-0.92) and recessive model (OR0.82; 95% CI 0.69-0.97). No publication bias was found. Conclusion Our meta-analysis confirmed a protective effect of C242T polymorphism on CAD in Asian population and indicated that A640G polymorphism was significantly associated with decreased risk of CAD.